Treatment methods of temporomandibular dysfunction: systematic review - Dutra, Laio da Costa; Seabra, Eduardo José Guerra; Dutra, Gláucya Raquel Souza da Fonseca; Silva, Alexandre Policarpo da; Martins, Yuri Victor de Medeiros; Barbosa, Gustavo Augusto Seabra (Journal of Health Care, 2016)
Introduction: Temporomandibular disorder (TMD) is a change generated by various disorders, that can affect the masticatory muscles, the temporomandibular joint, or both. Objective: Broach forms of treatment for TMD, as well as its interdisciplinary clinical management, in conducting a symptomatic TMD condition to permanent rehabilitation. Materials and Methods: This is a theoretical study of the systematic review type, based on literature review of electronic database of articles PubMed and Library Cochrane, conducted by three independent reviewers. This study included articles from January 2009 to January 2014. Results: We found 929 records, and selected thirteen studies. The verification of the material identified that the occlusal devices more used were the occlusal splint, followed by the front plateau. Within the drugs, ibuprofen and diazepam were found and used in the studies. Counselling, as changes in behavior, sleep posture, guidance on diet and inhibition of harmful oral habits were found. In multidisciplinary approach, acupuncture and laserterapia were found, which can lead to pain relief. Conclusion: It can be seen that the methods of treatment for TMD are accessible and diverse, being the professional's responsibility to choose the therapy that best fits the profile of patients after a correct planning.
Keywords: medication therapy management; temporomandibular joint dysfunction syndrome; dental occlusion; counseling; review.